2004
DOI: 10.1057/palgrave.fr.9400177
|View full text |Cite
|
Sign up to set email alerts
|

‘Big Sisters’ are Better Domestic Servants?! Comments on the booming au Pair Business

Abstract: The au pair program in general is still known as a form of cultural exchange program and a good possibility for young women to spend a year abroad, although it has undergone great changes during the last 10 years. This article argues that due to different socio-economic and cultural processes in Western postindustrial societies as well as in the eastern and southern parts of the world the au pair program is becoming a form of domestic work with quite similar working and living conditions to that of live-in mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 4 publications
1
27
0
2
Order By: Relevance
“…For domestic workers this aspect of the job can be a blessing -offering them the opportunity for emotional closeness and fulfilment in a situation which can otherwise be isolated (Lutz 2011) -but it can also be a curse as their status as workers is overlooked and their labour is cast as a duty or a favour (Cox and Narula 2003;Hess and Puckhaber 2004). Hubbies can find, however, that they are caught in the negotiation of gender roles and identities within families and it is to this aspect of 'hiring a hubby' that I turn now.…”
Section: Working Conditions In Traditionally Male Domestic Labourmentioning
confidence: 99%
“…For domestic workers this aspect of the job can be a blessing -offering them the opportunity for emotional closeness and fulfilment in a situation which can otherwise be isolated (Lutz 2011) -but it can also be a curse as their status as workers is overlooked and their labour is cast as a duty or a favour (Cox and Narula 2003;Hess and Puckhaber 2004). Hubbies can find, however, that they are caught in the negotiation of gender roles and identities within families and it is to this aspect of 'hiring a hubby' that I turn now.…”
Section: Working Conditions In Traditionally Male Domestic Labourmentioning
confidence: 99%
“…A review of international studies into this phenomenon shows that there are common prejudices, idioms, attitudes and behaviours in domestic employment relationships across the globe, in both developing and developed countries (Hansen 1990, 1992, Bakan and Stasiulis 1995, Stiell and England 1997, Romero 1998, Anderson 2001a, b, 2007, Hongagneu-Sotelo 2001, Mattingly 2001, Howell 2002, Lutz 2002, Qayum and Ray 2003, Hess and Puckhaber 2004, Muttarak 2004, Maher and Staab 2005, Mantouvalou 2006, Platzer 2006, Colombo 2007, Deguili 2007, Rodriquez 2007, Das Gupta 2008, Blofield 2009). Thus, for example, in a study of domestic workers in Thailand, Raya Muttarak (2004) found similar exploitation and abuse of domestic workers (themselves largely Thai) to that described in South Africa, with unpaid wages, physical abuse and insufficient food being common experiences for domestic workers.…”
Section: Domestic Employment Relationships Globallymentioning
confidence: 99%
“…Several studies have shown how this ambiguity allows the au-pair-receiving societies to be provided with low-cost domestic labour (see, e.g. Hess and Puckhaber 2004;Mellini et al 2007;Yodanis & Lauer 2005), raising frequent questions about the legitimacy of the au pair programme (see, e.g. Platzer 2002;Stenum 2008;Øien 2009).…”
Section: A Network-oriented Approach To Exploring Au Pair Trajectoriesmentioning
confidence: 99%